2009
DOI: 10.1038/ajg.2009.529
|View full text |Cite
|
Sign up to set email alerts
|

Stress Coping, Distress, and Health Perceptions in Inflammatory Bowel Disease and Community Controls

Abstract: Psychological health and IBD 2Background: This study compares a community IBD sample with a matched non-IBD community sample on psychological functioning and health perceptions. Methods:Participants in the population-based Manitoba IBD Cohort Study (n=388) were directly compared with sex, age, and region-matched controls from a national random-sample health survey on aspects of psychological health, coping, and perceived general health. Results:The IBD sample overall had lower psychological wellbeing and maste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
76
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 67 publications
5
76
0
3
Order By: Relevance
“…Such individuals may need to learn how to focus on those aspects of the disease that they can control to diminish any feelings of helplessness that may occur during this time. Th is may be an especially challenging task, given that Graff et al (1) found that avoidance coping tended to predominate during times when IBD was active.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
See 4 more Smart Citations
“…Such individuals may need to learn how to focus on those aspects of the disease that they can control to diminish any feelings of helplessness that may occur during this time. Th is may be an especially challenging task, given that Graff et al (1) found that avoidance coping tended to predominate during times when IBD was active.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…Th is may be the critical time for considering options that may help patients deal with this stress in more adaptive ways than by simply using various avoidant coping strategies as found by Graff et al (1) . Of particular concern was the tendency to blame oneself noted among those with active IBD in their study.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
See 3 more Smart Citations